2014
DOI: 10.1603/en14084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliage Color on the Landing Response ofPieris rapae(Lepidoptera: Pieridae)

Abstract: The effects of foliage color on the selection of host plants by Pieris rapae (L.) were investigated using choice tests between Brassica rapa (L.) varieties with green, variegated, and yellow-green leaves. Gravid-naive females displayed a first landing preference for the green and variegated Brassica varieties when the plants were freely accessible. Comparable results were observed when the plants were enclosed in glass jars, demonstrating that visual cues were sufficient to induce the landing response. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Both insect pollinators and herbivores use a wide range of sensory cues to locate their plant resources, for example, emitted volatile compounds (Harrewijn et al, 1994;Renwick and Chew, 1994;Knolhoff and Heckel, 2014), temperature (Seymour and Schultze-Motel, 1997;Angioy et al, 2004;Lamprecht et al, 2013), shape (Rausher, 1978;Mackay and Jones, 1989;Machial et al, 2012), and colour (Prokopy and Owens, 1983;Tsuji and Coe, 2014;Paris et al, 2015). The use of colour cues by insects has been studied intensely.…”
Section: Introductionmentioning
confidence: 99%
“…Both insect pollinators and herbivores use a wide range of sensory cues to locate their plant resources, for example, emitted volatile compounds (Harrewijn et al, 1994;Renwick and Chew, 1994;Knolhoff and Heckel, 2014), temperature (Seymour and Schultze-Motel, 1997;Angioy et al, 2004;Lamprecht et al, 2013), shape (Rausher, 1978;Mackay and Jones, 1989;Machial et al, 2012), and colour (Prokopy and Owens, 1983;Tsuji and Coe, 2014;Paris et al, 2015). The use of colour cues by insects has been studied intensely.…”
Section: Introductionmentioning
confidence: 99%
“…Since varietal and color richness vary independently from one another and are not collinear, these results demonstrate that P. rapae responded to intraspecific variation in crop color in addition to overall varietal richness. Previous studies have demonstrated that color is an important plant trait in moderating insect populations and P. rapae in particular is known to use foliage color as a landing cue (Tsuji and Coe 2014). In some instances, plant color is also correlated with plant defense compounds (Malenčić et al 2012, Green et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that color is an important plant trait in moderating insect populations and P. rapae in particular is known to use foliage color as a landing cue (Tsuji & Coe 2014). In some instances, plant color is also correlated with plant defense compounds (Malenčić et al 2012, Green et al 2015).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…potential oviposition sites can be detected with increasing probability. At least, a positive oviposition response to plant colouration has been observed explicitly in some diurnal insects, such as the butterflies, Pieris rapae (Ilse 1937;Tsuji and Coe 2014) and Papilio aegeus (Kelber 1999), and the flies, Delia radicum (Prokopy et al 1983) and Dacus oleae (Katsoyannos et al 1985).…”
Section: Introductionmentioning
confidence: 99%